Exploiting process thermodynamics in carbon capture from direct air to industrial sources: The paradigmatic case of ionic liquids - Sergio Dorado-Alfaro; Daniel Hospital-Benito; Cristian Moya; Pablo Navarro; Jesús Lemus; José Palomar (Carbon Capture Science & Technology)
The development of efficient and cost-effective carbon capture (CC) technologies is becoming a crucial challenge for short-term industrial decarbonization strategies and energy transition goals centred on biomethane and biohydrogen production. Nowadays, available CC technologies present main shortcomings for being applied to the huge wide range of CO2 partial pressure involved in currently-of-interest industrial CC scenarios (from 0.0004 bar in direct air capture to 13 bar in pre-combustion system: it means five orders of magnitude). Aprotic N-heterocyclic anion-based ionic liquids (AHA-ILs) arise as highly versatile CO2 chemical absorbents able to deal with this challenge. In this work, the process thermodynamic limits of the CC based on AHA-IL is explored by estimating the thermodynamic CO2 absorption cyclic capacity (zcyclic) for four relevant CC industrial systems [inlet CO2 partial pressure typical of direct air capture (DAC), post-combustion (post-comb), biogas upgrading (biogas) and pre-combustion (pre-comb)], by means of sensitivity analysis in the literature reported range of key material properties (reaction enthalpy, ΔHR: [−15, −100 kJ/mol]; reaction entropy, ΔSR: [−0.05, −0.16 kJ/mol⋅K]; Henry constant, KH: [20, 115 bar]) and process operating conditions (absorption temperature, Tabs: [20, 100 °C]; regeneration temperature, Treg: [20, 100 °C]; regeneration pressure, PCO2reg: [0.01, 0.5 bar]). It is obtained that zcyclic can be significantly increased by designing AHA-ILs with more negative ΔHR and ΔSR values, since reaction exothermicity enhances the absorption stage, whereas unfavourable reaction entropy promotes absorbent regeneration. Physical absorption contribution described by KH plays a minor role in post-comb and biogas CC systems and becomes highly relevant for pre-comb conditions; surprisingly, DAC process can be enhanced by decreasing the KH value of the material. Regarding the influence of process operating conditions, the CC cyclic capacity is improved by decreasing Tabs and PCO2reg and increasing Treg, but with remarkably different impact depending on CC scenario: zcyclic is barely affected in pre-comb system whereas process conditions are determinant for obtaining positive zcyclic values in DAC. Finally, the critical analysis of literature available ΔHR, ΔSR and KH reveals the great suitability of designing AHA-IL materials, by fine tuning the cation and anion structures, to develop innovative technology with improved CC process performance, particularly for more challenging DAC and diluted carbon source capture.